Pengembangan Modul Digital Flipbook Berbasis CTL (Contextual Teaching and Learning) pada Materi Ekosistem Siswa Kelas X SMA Negeri 2 Gowa - Fajri; Rahmatia Thahir; Hilmi Hambali (Mataram University, 2026)
This study aimed to develop a Contextual Teaching and Learning (CTL)-based digital flipbook module on ecosystem material for tenth-grade students of SMA Negeri 2 Gowa that is valid, practical, and effective for classroom learning. This research employed a Research and Development (R&D) approach using the ADDIE model, consisting of five stages: Analysis, Design, Development, Implementation, and Evaluation. The analysis stage involved identifying teachers’ and students’ needs as well as analyzing the Merdeka Curriculum implemented in the school. The developed product was a CTL-based digital flipbook module accessible through mobile devices and equipped with illustrations, learning videos, practice exercises, interactive quizzes, and group projects that connected learning materials with students’ real-life experiences. The validity of the product was evaluated by material and media experts, while practicality and effectiveness were assessed through field testing involving tenth-grade students of SMA Negeri 2 Gowa. Data were collected using validation sheets, teacher and student response questionnaires, and learning achievement tests. The data were analyzed descriptively using percentages and assessment criteria. The results indicated that the developed CTL-based digital flipbook module met the criteria of validity, practicality, and effectiveness, making it suitable for use as instructional material in ecosystem learning. Furthermore, the digital flipbook module enhanced student engagement, supported independent learning, and facilitated a more contextual and meaningful understanding of ecosystem concepts.